Inducing Immune Infringement: The Interplay of § 287(c) and § 271(b) - Moulton, Libby (Science and Technology Law Review, 2012)
When the Physician’s Immunity Statute was enacted in 1997, its statutory language and legislative history left open an important question—under what circumstances should the medical practitioner’s immunity be extended to the inducer of an infringement? This Article explores the relationship between the two patent statutes central to answering this question: the Physician’s Immunity Statute, 35 U.S.C. § 287(c), which grants immunity to medical practitioners who infringe a medical method patent, and the inducement statute, 35 U.S.C. § 271(b), which states that a patent holder may recover from a party who actively induces patent infringement. It concludes that there is indeed a conflict between the Physician’s Immunity Statute’s language and intent, especially when considered in conjunction with inducement statute’s policy of providing a useable remedy to infringement. To resolve this conflict, the Article lays out a proposed framework for courts to determine when an inducer should be held liable for the infringement of a medical method patent. Courts should carefully interpret the language of section 287(c), and limit section 271(b) in some settings, in order to give proper effect to the policy that section 287(c) expresses.